ARTIFICIAL INTELLIGENCE AS A LANGUAGE LEARNING PARTNER - Bekchanova Mahliyoxon Hamidjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:The rapid advancement of artificial intelligence (AI) has transformed various  aspects  of  modern  society,  particularly  the  field  of  education.  Language learning, which traditionally relied on textbooks, classroom instruction, and face-to-face interaction, is now increasingly supported by intelligent technologies. AI-powered applications, chatbots, virtual assistants, adaptive learning platforms, and automated assessment  systems  have  become  effective  tools  for  language  acquisition.  These technologies  provide  learners  with  personalized  learning  experiences,  immediate feedback,  continuous  practice  opportunities,  and  access  to  authentic  language resources.  As  a  result,  artificial  intelligence  is  no  longer  viewed  merely  as  a technological  innovation  but  as  an  active  learning  partner  that  supports  students throughout  their  educational  journey.  Students  can  practice  speaking,  listening, reading, and writing skills through interactive digital environments that adapt to their individual  needs  and  proficiency  levels.  This  article  examines  the  role  of  artificial intelligence as a language learning partner, discussing its advantages, challenges, and implications for the future of language education.